Genetic polymorphisms in cytokine genes in colombian patients with ocular toxoplasmosis (2018)
Toxoplasmosis is caused by infection with the protozoan parasite Toxoplasma gondii, which has the capacity to infect all warm-blooded animals worldwide. Toxoplasmosis is a major cause of visual defects in the Colombian population; however, the association between genetic polymorphisms in cytokine genes and susceptibility to ocular toxoplasmosis has not been studied in this population. This work evaluates the associations between polymorphisms in genes coding for the cytokines tumor necrosis factor alpha (TNF-?) (rs1799964, rs1800629, rs1799724, rs1800630, and rs361525), interleukin 1? (IL-1?) (rs16944, rs1143634, and rs1143627), IL-1? (rs1800587), gamma interferon (IFN-?) (rs2430561), and IL-10 (rs1800896 and rs1800871) and the presence of ocular toxoplasmosis (OT) in a sample of a Colombian population (61 patients with OT and 116 healthy controls). Genotyping was performed with the 'dideoxynucleotide (ddNTP) primer extension' technique. Functional-effect predictions of single nucleotide polymorphisms (SNPs) were done by using FuncPred. A polymorphism in the IL-10 gene promoter (-1082G/A) was significantly more prevalent in OT patients than in controls (P = 1.93e-08; odds ratio [OR] = 5.27e+03; 95% confidence interval [CI] = 3.18 to 8.739; Bonferroni correction [BONF] = 3.48e-07). In contrast, haplotype 'AG' of the IL-10 gene promoter polymorphisms (rs1800896 and rs1800871) was present at a lower frequency in OT patients (P = 7e-04; OR = 0.10; 95% CI = 0.03 to 0.35). The +874A/T polymorphism of IFN-? was associated with OT (P = 3.37e-05; OR = 4.2; 95% CI = 2.478 to 7.12; BONF = 6.07e-04). Haplotype 'GAG' of the IL-1? gene promoter polymorphisms (rs1143634, rs1143627, and rs16944) appeared to be significantly associated with OT (P = 0.0494). The IL-10, IFN-?, and IL-1? polymorphisms influence the development of OT in the Colombian population. ©2018 American Society for Microbiology.